Divorced from knowledge: Perceptions of Alimony Fairness in Relation to Educational Discrepancies - Michael Kothakota; Jessica Wery (Journal of Financial Therapy, 2024)
Spousal support or alimony is a cash transfer from one spouse to another after divorce. The amount awarded might seem arbitrary and unfair to either one or both individuals. The public often does not see the fact patterns associated with alimony awards or agreements, and their input may provide information to policymakers and decision-makers about what a fair amount of alimony might be. This study examines data collected from 1,285 U.S. participants randomly assigned to a vignette condition that details a hypothetical alimony scenario where one spouse supported the other spouse to gain education, resulting in significantly increased income prior to divorce. Analyses conducted included logistic regression to determine the likelihood a participant would suggest alimony be awarded. A multivariate Heckman selection model was also applied, suggesting that younger generations believe an educational discrepancy does not necessarily mean the person earning less money should have more alimony. T-tests indicate participants think men who are supported through their education should pay more than women who are. A comparison was made to three commonly used alimony formulas across the United States. Evidence suggests that financial therapists should be aware of the generational differences in how individuals might feel about paying or receiving alimony when there is an educational discrepancy.
Keywords: alimony; divorce; educational discrepancy; fairness; selection bias